2018
DOI: 10.1002/anie.201811202
|View full text |Cite
|
Sign up to set email alerts
|

Templating and Catalyzing [2+2] Photocycloaddition in Solution Using a Dynamic G‐Quadruplex

Abstract: We describe at emplating/covalent capture strategy that enables photochemical formation of 8cyclobutanes in one noncovalent assembly.T his process was characterized by experiment and quantum mechanical/molecular mechanics (ONIOM) calculations.Thus,KIand 16 units of 5'-cinnamate guanosine form aG -quadruplex where C = C p bonds in neighboring G 4 -quartets are separated by 3.3 ,e nabling [2+ +2] photocycloaddition in solution. This reaction is highyielding (> 90 %), regio-and diastereoselective.S ince all compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Molecular flasks and containers have previously been found to influence and enhance the photochemical [2+2] cycloadditions of selected olefin substrates in solution . Some cation–π interactions can also facilitate the formation of cyclobutanes in solution, and even a dynamic G‐quadruplex has been shown to serve as a supramolecular template for photodimerization …”
Section: Figurementioning
confidence: 99%
“…Molecular flasks and containers have previously been found to influence and enhance the photochemical [2+2] cycloadditions of selected olefin substrates in solution . Some cation–π interactions can also facilitate the formation of cyclobutanes in solution, and even a dynamic G‐quadruplex has been shown to serve as a supramolecular template for photodimerization …”
Section: Figurementioning
confidence: 99%
“…[12][13][14][15] Some cation-p interactions can also facilitate the formation of cyclobutanes in solution, [16] and even adynamic G-quadruplex has been shown to serve as as upramolecular template for photodimerization. [17] By taking advantage of the good solubility of discrete assemblies, [18,19] our recent investigations have demonstrated that supramolecular metallamacrocycles,e specially metalcarbene templates,a llow photochemical [2+ +2] dimerization of olefin-containing ligands in solution ( Figure 1a). [20] These scaffolds,although versatile,suffer from difficulties related to the removal of the template metal in the assembled systems, hampering the isolation of the formed cyclobutane derivatives.H erein we report the synthesis of an ew class of supramolecular metallacycles capable of undergoing photochemical reactions in solution ( Figure 1b).…”
Section: Supramolecularcontrolofphotocycloadditionshasemergedmentioning
confidence: 99%
“…[48] Thus, increasing the sensitivity of the halochromic response will also be critical for such applications outside the biological arena. Finally, it might be possible to dual gate photochemical reactivity not only with halochromaticity, but with an additional gate such as supramolecular templating [58] or organocatalysis activation, [59] opening avenues to safe-guarded photochemical responses for the forward reaction but possibly also for the reverse. Such dual gated photochemically induced debonding reactions could find use in fail-safe adhesives, [60] where two triggers have to come to together before release occurs.…”
Section: Discussionmentioning
confidence: 99%